2016
DOI: 10.4012/dmj.2016-062
|View full text |Cite
|
Sign up to set email alerts
|

Irradiation effects of low temperature multi gas plasma jet on oral bacteria

Abstract: The purpose of this study is to evaluate the sterilization effects of a newly developed low temperature multi gas plasma jet on oral pathogenic microorganisms (Streptococcus mutans [S. mutans], Lactobacillus fermentum [L. fermentum], Aggregatibacter actinomycetemcomitans [A. actinomycetemcomitans]). Plasma gas which generated from O2, N2, Ar and 50% (O2+N2) was irradiated to the microbes. Effect of O2 plasma irradiation on S. mutans under scanning electron microscopy (SEM) was also observed. O2 plasma was dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 17 publications
0
14
1
Order By: Relevance
“…Three studies investigated the effect of CAP on A. actinomycetemcomitans (Table 4). Direct application of argon plasma showed a non-significant reduction compared to the control group at a treatment time of less than 1 minute [19], but the numbers of CFU decreased to a non-detectable level after more than 10 minutes [56]. When using different working gases, the values of RF increased.…”
Section: Periopathogensmentioning
confidence: 85%
See 4 more Smart Citations
“…Three studies investigated the effect of CAP on A. actinomycetemcomitans (Table 4). Direct application of argon plasma showed a non-significant reduction compared to the control group at a treatment time of less than 1 minute [19], but the numbers of CFU decreased to a non-detectable level after more than 10 minutes [56]. When using different working gases, the values of RF increased.…”
Section: Periopathogensmentioning
confidence: 85%
“…Rupf et al showed reduction values of 4.5 log10 and more using a mixture of helium, nitrous oxide and oxygen [33]. Treating for up to 60 s with nitrous oxide resulted in 0.6-1 log10 CFU reduction, pure oxygen rendered values from 1.3 log10 to complete sterilization and a combination of both gases showed no reduction up to 0.9 log10 CFU [19].…”
Section: Lactobacillimentioning
confidence: 99%
See 3 more Smart Citations